Economic and biological characteristics of the new spring oats variety “Arkhan” - V. А. Korelina; О. B. Batakova; I. V. Zobnina; А. D. Kabashov (Зерновое хозяйство России, 2021)
The developed spring oats varieties should combine potential productivity with resistance to abiotic and biotic environmental factors due to increased adaptability. The purpose of the current study was to develop a new highly productive spring oats variety with a complex of economically valuable traits that are resistant to abiotic and biotic stressors. The current paper has presented a description of the new spring oats variety ‘Arkhan’ (mutika), developed by the Moscow RIA in cooperation with the FSEI “Kotlasskoe” by the method of individual-family selection from a hybrid population obtained from step hybridization of the varieties of different origin. The Competitive Variety Testing of the variety ‘Arkhan’ was carried out in 2013–2016 on the basis of the FSEI “Kotlasskoe” of the Arkhangelsk region, the variety ‘Krechet’ was the standard variety. The grain productivity of the new variety averaged 4.5 t/ha over 4 years, which was significantly larger than that of the standard variety ‘Krechet’ (3.5 t/ha). The average green mass productivity of the variety ‘Arkhan’ was 26.7 t/ha, which on 8.5 t/ha higher than that of the standard variety ‘Krechet’. The variety ‘Arkhan’ is characterized by resistance to head smut, being relatively resistant to crown oats rust. The variety is highly resistant to grain shedding and lodging. According to the best indicators, the new spring oats variety ‘Arkhan’ in 2017 was sent for the study to the State Variety Network of the Russian Federation. According to the results of the State Variety Testing, the variety has been included into the State List of Breeding Achievements approved for use on the territory of the Russian Federation since 2020 (in regions 1, 2, 3, 4 and 5).